A PROSPECTIVE OBSERVATIONAL STUDY OF EASTERN INDIAN CERVICAL CANCER SCREENING PRACTICES AND RELATED FACTORS - Kumari, Priti; Kumari, Usha (Student's Journal of Health Research Africa, 2024)
Background An estimated 120,000 Indian women are affected by uterine cervical cancer each year, which is a serious health issue for them. Although cervical cancer is less common in urban settings, it is still very common in rural areas. Objectives This study intends to evaluate the cervical cancer screening behaviors of women in Eastern India and pinpoint the sociodemographic characteristics linked to these practices. Materials and methods The design of the study was prospective which took place at the Jawahar Lal Nehru Medical College & Hospital, Bhagalpur, Bihar, India. The study has been conducted for 11 months, i.e., from 24th January 2019 to 31st December 2019. Overall, 125 patients were enrolled in the study. Results The average age of all the participants was 38.2±7.4. Most of the patients included in the study are from rural areas with 75 (60%), and the rest 50 (40%) are from urban areas. Most of the included patients were from middle-class families and the least were from high-class families. Age among participants who were screened and who were never screened was found to be significant. There was a significant difference observed between socioeconomic status and educational level between the groups of screened and not screened patients respectively. Conclusion The study concluded that Eastern India had below-optimal screening rates of cancer of the cervix, especially for women from rural areas, those with lower educational attainment, and those from lower socioeconomic backgrounds. Recommendations Campaigns to increase awareness, enhance access to screening facilities, and remove financial barriers, especially for underprivileged populations—should be the main focus of public health initiatives. Reducing the rate of cancer of the cervix in Eastern India, requires extending the reach of public health programs and incorporating cervical cancer screening into standard medical care.